Production of Tannase from Aspergillus niger under solid state fermentation - Mahdi, Zainab Saadi; Al-Tahan, Shatha Salman (Iraqi Journal of Science, 2023)
Thirteen A.niger isolates were obtained from soil and food samples and screened on tannic acid agar for their ability to produce tannase. There isolates revealed large tannic acid hydrolysis zones, these isolates were cultured in liquid and solid substrate fermentation media to examine their production of tannase quantitatively .Solid substrate medium was more efficient than liquid medium ,and A.niger Ass19 gave the highest tannase productivity. Different kinds of SSF media and cultured conditions were performed to determine their effect on tannase production. The maximum yield of tannase was obtained in wheat bran with tea leaves hydrated with citrate buffer pH 5.5 at 1:3 (w/v) hydration ratio inoculated with 2108 fungal spores and incubated at 28C for 72hr .the tannase productivity was 8200 U/mg at these conditions.